Accuracy of the strengths and difficulties questionnaire in identifying common mental health disorders in children and adolescents: a cross-sectional analytical study - Maisaa Al-Dhahri; Salim Al-Huseini; Maisa AL-Jamoudi; Sanjay Jaju; Samir Al-Adawi; Hassan Mirza (Discover Mental Health)
Abstract Background and aim This cross-sectional analytic study, conducted in the Child and Adolescent Mental Health (CAMH) Clinic of Sultan Qaboos University Hospital (SQUH) for 12 months, aimed to evaluate the precision of the Strengths and Difficulties Questionnaire (SDQ) in identifying hyperactivity disorder (ADHD), conduct problems, and emotional difficulties in children and adolescents in an Arab-speaking population. Method The study involved 139 participants aged 4 to 17 years drawn from new referrals to CAMH services. SDQ scores were compared with the gold standard clinical diagnosis obtained through diagnostic interviews based on the Diagnostic and Statistical Manual of Mental Disorders criteria. The predictive accuracy of SDQ subscales for attention deficit hyperactivity disorder (ADHD) and emotional difficulties was evaluated using Kendall's tau-b. Result The results indicated moderate agreement for emotional problems (Kendall's tau b 0.265; p < 0.001) and between moderate and strong agreement for hyperactivity problems (Kendall's tau b 0.351; p < 0.001). Screening efficiency indices, including sensitivity and positive predictive values, varied between the two disorders (sensitivity: 56–80%; positive predictive values: 40% to 56%). Conclusion The study underscores the importance of understanding the strengths and limitations of SDQ in clinical settings, providing valuable information for mental health assessments in children and adolescents.